Characteristics of Sexually Transmitted Infection (STI) Patients at the Tanggul Health Center in Jember Regency in the January-June 2023 Period - Krizdiana, Usqi (Scientific Journal of Dermatology and Venereology, 2024)
Introduction: The incidence of sexually transmitted infections (STIs) can expand as the risk factors increase that increase the transmission of STIs, including having unprotected sexual contact with multiple partners, having a history of STIs, having a history of sexual violence, alcohol use, prostitution, having sexual partners who have sexual contact. additional and concomitant or have a history of previous STIs, drug use, and use of intravenous drugs. This study aimed to present the characteristics of sexually transmitted infections in Tanggul Health Center, Jember Regency, Indonesia. Methods: This study is a descriptive observational study. A total of 52 research subjects participated in this study. Analysis of variable characteristics was carried out univariately with SPSS version 25. Results: The highest prevalence of STIs was gonorrhea, namely 20 people (38.46%), the age group with the most STIs, namely 25-49 years, as many as 36 people (69.23%), sex of STI sufferers the most were men, 37 people (71.15%) and the risk factors for experiencing STIs that were most common were customers of sex workers, 31 people (59.61%). Conclusion: This study revealed the characteristics of STI patients at Tanggul Health Center. Gonorrhea was the highest prevalence STI and most of patients were male and had sexual contact history with prostitutes.